Engendered Heritage: Shakespeare's Illyria Travested - Čale Feldman, Lada (Array, 1998)
The chronotope Illyria in Shakespeare's Twelfth Night, a reference to an actual geographic space and the time, namely to the Dalmatian coast and the territory of the Dubrovnik Republic, is connected here with the festive background of the play, particularlz with the motif of crossdressing, carnival inversion of gender roles, also a characteristic of the Dalmatian carnivals, especially those in the Dubrovnik region.